Highly efficient and stable cryo-ground sulphur cathode for Li-S batteries - Kazda, T.; Krbal, Miloš; Pouzar, Miloslav; Vondrak, J.; Strakova, A. Fedorkova; Slavik, M.; Wágner, Tomáš; Macák, Jan (Elsevier Science BV, 2016)
Here we report on a Li-S battery with cathode, based on a S powder obtained from bulk amorphous S, by cryogenic grinding. The cathode was prepared from a slurry, wherein the content of cryo-ground S powder was equal to 80 wt % (corresponds to approximate to 2.26 mg cm(-2)). Other slurry components included carbon Super P, and polyvinylidene fluoride, dispersed in N-methylpyrrolidone. The electrochemical performance of the as-prepared battery was compared to a battery based on an identically prepared paste, but containing reference S powder (with the orthorhombic structure). A longer life cycle, and enhanced capacity per gram, as well as per cm(2) of electrode was revealed for the cryo-ground S-based cathode. The electrochemical results show that the loss in capacity of the cryo-ground S powder cathode was just 3% after 50 cycles, which suggests on a higher stability of S inside the cathode during cycling.
Vysoce účinná a stabilní katoda z kryogenně mleté síry pro Li-S baterie
Keywords: Lithium-sulphur battery; Sulphur cathode; Cryogenic grinding; Li-ion batteries; Li-S baterie; katoda na bázi síry; kryogenní mletí; Li-ion baterie